PENGARUH ADIKSI GAME ONLINE MOBILE LEGEND TERHADAP KECERDASAN EMOSIONAL SISWA - Putri Yuliana; Titik Haryati (LPPM Institut Pendidikan Nusantara Global, 2023)
This research was conducted with the aim of examining the Effect of Mobile Legend Online Game Addiction on the Emotional Intelligence of Students of SMAN 44 Jakarta. The Mobile Legend Online Game was chosen because it is considered to have a significant influence on students' emotional intelligence in the ever-developing digital technology era. The population of this study were students of class XI at SMAN 44 Jakarta as subjects in this study, with a total of 68 students divided into 6 classes (3 classes XI IPS and 3 classes XI MIPA), each class consisting of 36 students. The research sample was taken using purposive sampling technique and using observation and questionnaires as data collection tools. The results showed that there was a significant influence between online legend mobile game addiction and students' emotional intelligence. This can be seen from the results of statistical calculations, where the Fcount value of 15,328 exceeds the Ftable of 3.98 with a significance level of 0.001 <0.05. based on the established criteria, Ha's hypothesis which states addiction to online mobile legend games has an influence on emotional intelligence is accepted. The mobile legend online game addiction variable has an influence of 1.88%, while other factors not included in the research model can also affect emotional intelligence.